Pressure tolerant nanocrystalline Se85-xTe15Gax(x=0, 2, 6, 10, 15) semiconductor. (2016) - Chaudhary, Neeru; Prasad, K.N.N.; Goyal, Navdeep
Abstract: The synthesis of Se85-x Te15 Gax (x=0, 2, 6, 10, 15) nanocrystalline material and its resistance change under pressure is reported in this paper. The Se85-x Te15 Gax (x=0, 2, 6, 10, 15) nanocrystalline material has been synthesized through melt and quench technique. Resistance change was studied under pressure (0-10 GPa) in Bridgman opposed anvil cell. The variations in resistance at different pressures were recorded. The relative resistance change is very small in the experimental range. This has given its application as a strong contender for fabricating solid state devices in Pressure Tolerant Electronics.